Osteoporosis knowledge among future healthcare practitioners: Findings from a Malaysian public university - Elnaem, Mohamed Hassan Abdelaziz; Jamshed, Shazia Qasim; Elkalmi, Ramadan Mohamed Mahmod; Baharuddin, Muhammad Farhan; Johari, Muhammad Afif; Ab Aziz, Nur Ashikin; Ahmad Sabri, Siti Farhanah; Ismail, Nur Akmal (Wolters Kluwer - Medknow, 2017)
Background and Objectives: Students in relevant health‑care academic programs are the future professionals who should play an active role in increasing community awareness regarding chronic diseases such as osteoporosis. This research aimed to evaluate the knowledge of osteoporosis, one of the growing health‑care burdens in Malaysia, among students belong to three different health occupations programs in a Malaysian University. Methods: A cross‑sectional study design was conducted to assess the level of knowledge on osteoporosis and to explore the potential association between the study program and osteoporosis‑related knowledge among medicine, pharmacy, and allied health sciences students in a Malaysian University. A total of 348 students were approached. The data were collected using validated revised Osteoporosis Knowledge Test questionnaire. Results: The results showed variability in knowledge score between students belonging to different study programs. allied health sciences students have the highest overall total score (median = 20) and nutrition score (median = 16), but for exercise score, both students in allied health sciences and medicine programs shared a similar median score (median = 11.5). More than half of the respondents showed adequate knowledge on osteoporosis. The students from allied health sciences exhibited more knowledge on osteoporosis compared to students in other study programs. Among the Kulliyyah of Pharmacy respondents, the majority did not manage to answer correctly on the whole scale. This was evident by total percentage of 69.91% of the respondents scored below than median score. Conclusion: There is a considerable gap of knowledge regarding osteoporosis among students in various health occupations academic programs. Pharmacy students particularly need focused learning related to exercise and nutrition in preventing osteoporosis during their academic program.